Intermediate algebra - Johnston, C.L. (Wadsworth Pub. Co, 1995)
This traditional, straight-forward, extremely popular book helps students learn algebra concepts-by using a one-step, one-concept-at-a-time approach. All major topics are divided into small sections, each with its own examples and often with its own exercises--an approach that helps students master each section before proceeding on to the next